Effect of steel fibers on the ultimate flexural behavior of dapped-end connections. (15th May 2022) - Mihaylov, Boyan; Rajapakse, Chathura; Berger, Paul-Hadrien
Highlights: A kinematics-based model for the flexural strength of FRC dapped-ends is proposed. Additional tensile resistance due to fibers is modelled. Enhanced ductility of the concrete in the compression zone is modelled. Effect of fiber volumetric ratio and shape of fibers is demonstrated. Possibility of reducing the conventional reinforcement amount is demonstrated. Abstract: Dapped-end connections in reinforced concrete structures work with high shear stresses and require dense reinforcement to ensure sufficient load-bearing capacity. In addition, under service loads, such connections typically develop inclined cracks that propagate from the re-entrant corner of the connection. In order to reduce the amount of reinforcement while enhancing the crack control, researchers have studied the use of fiber-reinforced concrete (FRC). However, while lab tests have shown that steel fibers can be very effective, there is a lack of rational mechanical models for FRC dapped-end connections. This paper proposes such a model based on kinematics, constitutive relationships, and equilibrium. The model accounts for two effects associated with the fibers: tension across the critical re-entrant corner cracks and enhanced ductility of the compression zones. FRC dapped-end tests from the literature are used to establish key modelling assumptions regarding the kinematics of the connections and to validate the proposed model. For 26 specimens, the average experimental-to-predicted strength ratio of the proposed model is 1.09 and the coefficient of variation is 10.6%. Using the kinematics-based model the effects of the fiber volumetric ratio and the shape of fibers on the ultimate flexural capacity of FRC dapped-end connections is investigated. For the studied cases, it was demonstrated that the effect of the end hooks can be significant, with the strength contribution of fibers more than doubled due to the hooks for a fiber volumetric ratio of 1.25%. The model is also used to investigate how the fibers can be used to reduce the amount of conventional reinforcement required against flexural failures.